2018
DOI: 10.31910/rudca.v21.n2.2018.1083
|View full text |Cite
|
Sign up to set email alerts
|

Capacidad antioxidante y antimicrobiana de tubérculos andinos (Tropaeolum tuberosum y Ullucus tuberosus)

Abstract: Artículo de acceso abierto publicado por Revista U.D.C.A Actualidad & Divulgación Científica bajo una licencia Creative Commons CC BY-NC 4.0 Palabras clave: biocomponentes, cultivos autóctonos, ulluco, cubio, papalisa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 4 publications
0
1
0
1
Order By: Relevance
“…Furthermore, Mejía-Lotero et al (2018) evaluated the antioxidant and antimicrobial activity in Tropaeolum tuberosum and Ullucus tuberosus, where a high percentage of antioxidant activity was found in all parts of the plants (leaves, stem, and tuber), mainly in plants treated with elicitors. On the other hand, Cham et al (2021) reported a significant difference (P≤0.05) between the treatments in the tomato "Saladette" Cultivar elicitors Activane ® (T2) and Micobiol ® (T3) with the highest of the DPPH scavenging activity in tomato fruits.…”
Section: Enzymatic Activity Of Polyphenol-oxidase and Dpph Antioxidan...mentioning
confidence: 99%
“…Furthermore, Mejía-Lotero et al (2018) evaluated the antioxidant and antimicrobial activity in Tropaeolum tuberosum and Ullucus tuberosus, where a high percentage of antioxidant activity was found in all parts of the plants (leaves, stem, and tuber), mainly in plants treated with elicitors. On the other hand, Cham et al (2021) reported a significant difference (P≤0.05) between the treatments in the tomato "Saladette" Cultivar elicitors Activane ® (T2) and Micobiol ® (T3) with the highest of the DPPH scavenging activity in tomato fruits.…”
Section: Enzymatic Activity Of Polyphenol-oxidase and Dpph Antioxidan...mentioning
confidence: 99%
“…La piel del olluco puede tener una gran cantidad de colores como amarillo, naranja, rojo, magenta y púrpura, con o sin pecas de color; cuya pigmentación es debida a colorantes naturales y funcionales llamados betalaínas [3], [4]. En este trabajo se usaron dos morfotipos de color amarillo (Quello lisa) y color rosa (Puka lisa).…”
Section: Introductionunclassified